2008
DOI: 10.1136/ard.2008.092585
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab effectively reduces the rate of anterior uveitis flares in patients with active ankylosing spondylitis: results of a prospective open-label study

Abstract: Objective:To evaluate the effect of adalimumab on the frequency of anterior uveitis (AU) flares in patients with active ankylosing spondylitis (AS).Methods:We determined the history of ophthalmologist-diagnosed AU in 1250 patients with active AS who were enrolled in a multinational, open-label, uncontrolled clinical study of treatment with adalimumab, 40 mg every other week for up to 20 weeks. All AU flares were documented throughout the adalimumab treatment period plus 70 days. We compared the rates of AU fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
4
24

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(160 citation statements)
references
References 30 publications
(29 reference statements)
6
126
4
24
Order By: Relevance
“…Regarding the rate of uveitis flares on monotherapy with ADA, in our study this is with 37 per 1,000 patient-years, actually lower than 150 per 1,000 patient-years in the phase III ADA study for spondyloarthritis (25) and 140 per 1,000 patient-years in the prospective observational study in spondyloarthritis patients (28). Since there is no information available about the uveitis rate per patient-year before treatment in the BIKER registry, it is not possible to decide whether the rate decreased under ADA.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Regarding the rate of uveitis flares on monotherapy with ADA, in our study this is with 37 per 1,000 patient-years, actually lower than 150 per 1,000 patient-years in the phase III ADA study for spondyloarthritis (25) and 140 per 1,000 patient-years in the prospective observational study in spondyloarthritis patients (28). Since there is no information available about the uveitis rate per patient-year before treatment in the BIKER registry, it is not possible to decide whether the rate decreased under ADA.…”
mentioning
confidence: 87%
“…In 12 JIA patients treated with ADA, Simonini et al showed that those stayed in remission for a longer time compared to JIA patients on infliximab (24). In a phase III study of spondyloarthritis, while not aiming for uveitis treatment, it could be demonstrated that the flare rate dropped from 15 per 100 patient-years in 1,250 patients pretreatment to 7.4 per 100 patient-years undergoing treatment (25). In a long-term followup over 24 months in 94 patients with JIA-associated uveitis, Kotaniemi et al observed a good response in 65% of patients (26).…”
mentioning
confidence: 99%
“…45 Adalimumab ile Behçet hastal›¤› d›fl›nda psoriazis, JIA, ankilozan spondilit gibi farkl› endikasyonlarda intraoküler inflamasyonun baflar› ile kontrol edilebildi¤i bildirilmifltir. 35,36,47,48 Biester ve ark. 49 çocukluk ça¤› üveitlerinde yapt›klar› bir çal›flmada, 17'sinde JIA, birinde ise idiopatik üveit bulunan 18 olguluk serilerinde adalimumab ile üveitin tamamen kontrol alt›na al›nma s›kl›¤›n› %88,8 (16/18) bildirmifllerdir.…”
Section: Tnf Antagonistleriunclassified
“…Rudwaleit и соавт. [16] проанализировали оф-тальмологические диагнозы у 1250 пациентов с актив-ным АС, принимавших участие в открытом неконтро-лируемом клиническом исследовании адалимумаба. Авторы сравнивали частоту обострений переднего уве-ита в течение 1 года до лечения адалимумабом и во вре-мя лечения.…”
Section: эффективность антагонистов фно α α в лечении увеитаunclassified